2020
DOI: 10.3390/mi11030249
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Quantifying Both Young’s Modulus and Specific Membrane Capacitance of Bladder Cancer Cells with Different Metastatic Potential

Abstract: Both Young’s modulus and specific membrane capacitance (SMC) are two important physical parameters for characterizing cell status. In this paper, we utilized a thin-neck-micropipette aspiration system to simultaneously quantify Young’s modulus and SMC value of six types of cell lines in different progression grades, which include four grades from the lowest metastatic potential G1 to the highest potential G4. We investigated how these two physical properties possess heterogeneities in bladder cancer cells with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Our findings embed this result in a greater perspective of a mechanical patterning mechanism that explains not just single folds, but entire lesions. They also align with studies that have demonstrated that BC cells from more aggressive origin are softer than cells from less aggressive BC origin [53][54][55]. The upregulation of type I and III collagen genes, predominantly found in the LP [62], is considered a marker for increased ECM stiffness and linked to BC invasion [37].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our findings embed this result in a greater perspective of a mechanical patterning mechanism that explains not just single folds, but entire lesions. They also align with studies that have demonstrated that BC cells from more aggressive origin are softer than cells from less aggressive BC origin [53][54][55]. The upregulation of type I and III collagen genes, predominantly found in the LP [62], is considered a marker for increased ECM stiffness and linked to BC invasion [37].…”
Section: Discussionsupporting
confidence: 84%
“…Our numerical simulations demonstrate that the buckling pattern can be explained by stiffness changes in the different layers of the mucosa. Softening of urothelial cells [53][54][55] and the upregulation of different ECM-related genes, linked to stiffening of the LP [37,56,57], have been investigated in BC and recognised as a risk factor for progression and invasion in BC. We were interested in investigating whether BC would also cause a change in stiffness in the BM.…”
Section: Basement Membrane Softens Locally In Bbn Treated Micementioning
confidence: 99%
“…Using these relationships, they identified the properties of different particles. Liu et al [9] used the micropipette system to obtain the elasticity modulus and the Specific Membrane Capacitance (SMC) of six bladder cancer cells. Choi et al [10] determined the elastic and viscous properties of human scleral collagen by ultrasonic elastography.…”
Section: -Introductionmentioning
confidence: 99%
“…Therefore, SJI-001 exhibits surface conditions suitable for cell culture and is applicable for several applications for cell assay and analysis. Liu and Yue et al [ 5 ] utilized a thin-neck-micropipette aspiration system to simultaneously quantify Young’s modulus and the specific membrane capacitance (SMC) value of six types of bladder cancer cell lines in different progression grades from the lowest metastatic potential G1 to the highest potential G4. The combination of these two physical properties on a scatter diagram clearly shows the cell groups with different cancer grades, which means that this combination could be a potential tumor grading marker to identify cancer cells with different metastatic potential.…”
mentioning
confidence: 99%